Ocena możliwości podziemnej retencji wód w zlewni potoku Rybnik w Sękowej - Dendys, Marta (My University, 2012)
Nowadays the problem of providing water for municipal needs of the population refers to both large cities and small towns, therefore local governments, scientists and entrepreneurs take on the task of meeting the growing demand. The aim of this study was to identify the hydrogeological conditions and the possibilities for underground storage of water in the village near Gorlice Sękowa, whose inhabitants are struggling with periodic water service interruptions. This object is achieved by the hydrogeological mapping of the terrain and numerical simulation of the hydrogeological conditions and possible options for water abstraction from the groundwater basin stream Rybnik. In the thesis there were also presented alternative solutions to the problem with their assessment. Assessment of these prepared solutions and simulations results were carried out in terms of environmental and economic aspects. The results show that there are no possibilities of water storage in the village Sękowa, but there are other effective ways to provide the required amount of water, which were proposed in this thesis.

Problem dostarczenia wody na potrzeby komunalne ludności dotyczy obecnie zarówno dużych aglomeracji miejskich, jak i małych miejscowości, a lokalne władze, naukowcy oraz przedsiębiorcy podejmują się zadania odpowiedzi na rosnące zapotrzebowanie. Celem niniejsze pracy było rozpoznanie warunków hydrogeologicznych oraz określenie możliwości podziemnego magazynowania wód w miejscowości Sękowa k. Gorlic, której mieszkańcy zmagają się z okresowymi przerwami w dostawach wody. Zadanie to zrealizowano poprzez zdjęcie hydrogeologiczne badanego terenu oraz odwzorowanie na modelu numerycznym warunków hydrogeologicznych i symulację możliwych wariantów poboru wód ze zlewni potoku Rybnik. W pracy podano także alternatywne rozwiązania problemu wraz z ich oceną. Ocena tych rozwiązań oraz przygotowane symulacje przeprowadzono w ujęciu aspektów środowiskowych i ekonomicznych. Otrzymane wyniki wskazują, że w sytuacji hydrogeologicznej miejscowości Sękowa niemożliwym jest magazynowanie wód, jednak istnieją skuteczne sposoby na zapewnienie wymaganej ilości wody, odpowiadającej zapotrzebowaniu mieszkańców.
Assessment of the possibilities of underground water retention in the groundwater basin of the Rybnik stream in Sękowa
Keywords: wody podziemne; zlewnia; zasoby wodne; eksploatacja; groundwaters; groundwater basin; water resources; groundwater exploitation